2017
DOI: 10.5194/piahs-375-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of gully erosion in Udmurt Republic, Russia

Abstract: Abstract. This article presents results from the long term-monitoring of gully headcut retreat rates (GHRR) between 1959 and 2015 in different parts of the Udmurt Republic and is based on the use of historical aerial photographs and field observations (measuring the distance from the gully head to a fixed reference point) ( Vanmaercke et al., 2016). It was determined that GHRR decreased from 2.4 to 0.3 m yr −1 during the 1959-1997 observation period and the 1998-2015 period, respectively. Measurements of GHRR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…It is well‐known that gully head retreat rates on agricultural lands directly depend from surface runoff (Poesen, Nachtergaele, Verstraeten, & Valentin, ). The decreasing trend was found for the gully headcut retreat rates within the Transect 1 (Figure ) during 1978–2015 (Rysin, Grigoriev, Zaytseva, Golosov, & Sharifullin, ). Similar reduction of gully headcut retreat rates is observed in the Kaluga region located in south‐western part of forest zone (S.I.…”
Section: Resultsmentioning
confidence: 88%
“…It is well‐known that gully head retreat rates on agricultural lands directly depend from surface runoff (Poesen, Nachtergaele, Verstraeten, & Valentin, ). The decreasing trend was found for the gully headcut retreat rates within the Transect 1 (Figure ) during 1978–2015 (Rysin, Grigoriev, Zaytseva, Golosov, & Sharifullin, ). Similar reduction of gully headcut retreat rates is observed in the Kaluga region located in south‐western part of forest zone (S.I.…”
Section: Resultsmentioning
confidence: 88%
“…The mean contribution of snow‐melting (1) and rainstorms (2) to mean annual gully head retreat rates (expressed as percent of the mean annual retreat rate) for two timeframes of monitoring: 1978–1997 and 1998–2014. Percentages are based on the results of monitoring campaigns in Udmurt Republic for sites located nearby Izhevsk (see Figure ) (after Rysin et al ., ). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 97%
“…This is supported by the results of the surface runoff monitoring from arable lands during spring snowmelt undertaken at the Novosil experimental station (the north of the forest‐steppe zone, to the west of the Middle Volga region), which showed a ten‐fold reduction in runoff coefficients since 1990 as compared to the period 1955–1980 (Petelko et al ., ). This trend concurs with observed reductions in gully headcut retreat in the Udmurt region, based on long‐term observations (1978–2015; Figure ; Rysin et al ., , , ). For gullies within cultivated catchments, it was found that average annual headcut retreat rates reduced from 1.5 m yr −1 (1978–1997) to 0.3 m yr −1 (1997–2015).…”
Section: Resultsmentioning
confidence: 99%
“…volume of sediment delivered from a gully mouth over a unit of time divided by a gully catchment area (m 3 ·km -2 ·yr -1 ). This parameter characterizes the amount of sediment delivered from gullies into the larger elements of a fluvial network (Rysin 1998):…”
Section: Methodsmentioning
confidence: 99%
“…Despite strong fluctuations in gully headcut retreat rates between individual years, their tendency to decrease is observed in most of the long-cultivated regions of the Volga River Basin (Rysin 1998). It should be noted, however, that this tendency is most applicable for gullies being developed on former arable land for relatively long periods (up to 200-300 years) and presently reaching a quasi-stable state.…”
Section: The Volga River Basinmentioning
confidence: 96%